Legal Intelligence: Integrating Knowledge and Strategy n Modern Legal Practice - Jennifer Ingelyne Nussy (PT. Hafasy Dwi Nawasena, 2026)
The rapid advancement of artificial intelligence and data-driven technologies has fundamentally transformed the landscape of modern legal practice. Legal intelligence, defined as the systematic integration of legal knowledge with strategic analytical capacities, has emerged as a critical paradigm for legal professionals navigating an increasingly complex regulatory and transactional environment. This article examines how the convergence of artificial intelligence, natural language processing, knowledge graph systems, and predictive analytics reshapes the foundational competencies required for effective legal practice. Through a normative juridical methodology, this research analyses the theoretical constructs underpinning legal intelligence and the practical frameworks through which these tools are deployed in legal research, judgment prediction, contract management, and risk assessment. The article identifies a central novelty: whereas prior literature has examined AI in law primarily from a technological or singular-domain perspective, this work provides a synthesised framework that integrates epistemic, strategic, and ethical dimensions of legal intelligence as a unified professional competency. Key findings indicate that successful integration requires not merely technological adoption but structural transformation in legal reasoning, institutional governance of AI systems, and recalibrated ethical obligations. The article concludes with normative recommendations for developing legally intelligent practice environments that remain accountable, transparent, and just.